Perencanaan Karir Pengguna Narkoba di Rehabilitasi - Desiana, Lilis; Ismanto, Heri Saptadi; Ismah, Ismah (Universitas PGRI Semarang, 2026)
Drug misuse produces physical, psychological, and social consequences that often weaken individuals’ capacity to plan their future, including their career direction. Career planning becomes particularly challenging for individuals in recovery, as they frequently face reduced self-confidence, limited skills, and difficulties identifying realistic career pathways. This study aims to explore the career planning abilities of individuals undergoing rehabilitation from drug use. A qualitative approach was employed, using in-depth interviews, observations, and documentation involving two primary participants and one supporting informant. Data were analyzed through coding, categorization, and thematic interpretation. The findings show varying levels of career planning across four dimensions: self-awareness, educational awareness, career awareness, and career exploration. Participants demonstrated improved reflection, motivation, and willingness to change; however, obstacles remained in identifying educational options, accessing relevant skill development, and formulating concrete career goals. The study also reveals that supportive counseling contributes to strengthening career readiness, though the available interventions are not yet systematic. Overall, the research indicates that career planning among individuals recovering from drug misuse shows positive development but still requires structured guidance to enhance independence and reduce relapse risks after completing rehabilitation.